Using a task force organization to achieve urgent development goals - Brady, James R. (1993)
A special task force is a temporary action organization designated to implement urgent priority programs in cases where governmental systems are unavailable, inadequate, or ineffective. Its creation anchors on the assumption that it will pursue a more aggressive role in the execution of its task within a given time frame. Inevitably expected to self-destruct upon the accomplishment of its stint, the task force as an implementing arm has the major advantage over government agencies in that it does not suffer from natural rigidity that oftentimes characterize permanent organizations. However, to enable it to function effectively and efficiently, it should operate under a legal mandate that legitimizes the use and procurement of resources.
Keywords: Task performance; Organizational performance